What Is Moderate to Vigorous Exercise Intensity? - MacIntosh, Brian R.; Murias, Juan M.; Keir, Daniel A.; Weir, Jamie M. (Frontiers in Physiology, 2021)
A variety of health benefits associated with physical activity depend upon the frequency, intensity, duration and type of exercise. Intensity of exercise is the most elusive of these elements and yet has important implications for the health benefits and particularly cardiovascular outcomes elicited by regular physical activity. Authorities recommend that we obtain 150 min of moderate to vigorous intensity physical activity (MVPA) each week. The current descriptions of moderate to vigorous intensity are not sufficient and we wish to enhance understanding of MVPA by recognition of important boundaries that define these intensities. There are two key thresholds identified in incremental tests: ventilatory and lactate thresholds 1 and 2, which reflect boundaries related to individualized disturbance to homeostasis that are appropriate for prescribing exercise. VT2 and LT2 correspond with critical power/speed and respiratory compensation point. Moderate intensity physical activity approaches VT1 and LT1 and vigorous intensity physical activity is between the two thresholds (1 and 2). The common practice of prescribing exercise at a fixed metabolic rate (# of METs) or percentage of maximal heart rate or of maximal oxygen uptake (V ̇O2max) does not acknowledge the individual variability of these metabolic boundaries. As training adaptations occur, these boundaries will change in absolute and relative terms. Reassessment is necessary to maintain regular exercise in the moderate to vigorous intensity domains. Future research should consider using these metabolic boundaries for exercise prescription so we will gain a better understanding of the specific physical activity induced health benefits.